2021
DOI: 10.1080/13691058.2021.1957151
|View full text |Cite
|
Sign up to set email alerts
|

Improving menstrual equity in the USA: perspectives from trans and non-binary people assigned female at birth and health care providers

Abstract: Menstruation research has largely focused on addressing menstrual management barriers facing cisgender women and girls in low and middle-income countries. Scant literature has assessed the menstrual management needs of trans and non-binary people assigned female at birth. To better understand these frequently invisibilised menstruation-related needs, we conducted a multimethod qualitative study in New York City which included: 17 indepth interviews across trans and non-binary people (n ¼ 10) and health care pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 37 publications
(40 reference statements)
0
21
0
1
Order By: Relevance
“…We were not able to determine the reasons behind this distress, but studies in TGD adults have shown that the use of menstrual products, experiencing menstrual symptoms such as dysmenorrhea or breast tenderness, and using male public restrooms in the absence of appropriate sanitary item disposal facilities can cause dysphoria. 6,19,20 In our study, 24.7% of adolescents were on menstrual suppression at their initial visit to our gender service. In a retrospective study of 133 TGD adolescents, Schwartz et al 10 reported that 14% were on menstrual suppression at their initial visit to their gender clinic, a rate that is similar to the 14.4% that we previously observed at our institution during the initial introduction of FASST.…”
Section: Discussionmentioning
confidence: 62%
“…We were not able to determine the reasons behind this distress, but studies in TGD adults have shown that the use of menstrual products, experiencing menstrual symptoms such as dysmenorrhea or breast tenderness, and using male public restrooms in the absence of appropriate sanitary item disposal facilities can cause dysphoria. 6,19,20 In our study, 24.7% of adolescents were on menstrual suppression at their initial visit to our gender service. In a retrospective study of 133 TGD adolescents, Schwartz et al 10 reported that 14% were on menstrual suppression at their initial visit to their gender clinic, a rate that is similar to the 14.4% that we previously observed at our institution during the initial introduction of FASST.…”
Section: Discussionmentioning
confidence: 62%
“…No gender diverse individuals reportedly participated in this study, although the perspectives of transgender students are important. More research is required on the experience and needs of this group who may experience a range of menstruation-related stressors at school not experienced by cisgender female-identifying students (Lane et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The use of toilet paper and not using products to manage menstruation was significantly more common among trans people and non-binary people, compared to cis participants and those identifying their gender as women. Acknowledging the needs and preferences of trans, intersex and non-binary people who menstruate is crucial [ 25 , 26 ]. Besides, distress among non-binary, intersex and trans people who menstruate resulting from packaging and advertising of menstrual products portraying menstruation as to represent “hegemonic femininity”, and the fact that many menstrual products need to be inserted in the vagina has already been discussed [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%